2017
DOI: 10.1158/0008-5472.can-16-2874
|View full text |Cite
|
Sign up to set email alerts
|

MCAM Mediates Chemoresistance in Small-Cell Lung Cancer via the PI3K/AKT/SOX2 Signaling Pathway

Abstract: Despite favorable responses to initial therapy, SCLC relapse occurs within a year exhibiting a multidrug resistant phenotype. Due to limited accessibility of patient tissues for research purpose, SCLC patient derived xenografts (PDXs) have provided the best opportunity to address this limitation. We sought to identify novel mechanisms involved in SCLC chemoresistance. Through in-depth proteomic profiling, we identified MCAM as a markedly upregulated surface receptor in chemoresistant SCLC cell lines that exhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 52 publications
2
78
0
Order By: Relevance
“…A study by Zabouo and colleagues also reported that MCAM expression was a poor prognostic indicator in human breast tumors . In small‐cell lung cancer, it had been reported that MCAM mediated chemoresistance via regulating the PI3K/AKT/SOX2 pathway . Up to now, the interrelationship and possible regulatory effects of Notch and MCAM in breast cancer remain not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Zabouo and colleagues also reported that MCAM expression was a poor prognostic indicator in human breast tumors . In small‐cell lung cancer, it had been reported that MCAM mediated chemoresistance via regulating the PI3K/AKT/SOX2 pathway . Up to now, the interrelationship and possible regulatory effects of Notch and MCAM in breast cancer remain not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the role of SOX2 on inducing ABCC1 expression, [22][23][24] but no direct evidence confirms this function of SOX2 until now. Here, the induction of SOX2 increased mRNA and protein levels of ABCC1 in the five melanoma cell lines ( Figure 4A,B),…”
Section: Sox2 Transactivates Abcc1 In Melanoma Cellsmentioning
confidence: 89%
“…heterogeneity) and the ability to switch among them (i.e. plasticity) (Huang, Jolly et al 2015, Mooney, Talebian et al 2017, Tripathi, Fahrmann et al 2017, Jolly, Preca et al 2018, Saha, Kumar et al 2018.…”
Section: Computational Methods To Identify Cscsmentioning
confidence: 99%